Triple-Divided Concha Bullosa: A New Anatomic Variation - Turhan San; Barış Erdoğan; Bülent Taşel (Case Reports in Otolaryngology)
In recent years, with the widespread use of imaging techniques such as paranasal sinus computed tomography (CT), many variations of nasal turbinates have been described. One of these variations known as concha bullosa (CB) is pneumatization of nasal turbinates. CB is the most frequently encountered anatomical variations of the middle turbinate. The term of septated concha bullosa has been described recently and it is an uncommon pneumatization anomaly of the middle turbinate. There has not been any study that correlates the number of septations and the presence of sinonasal pathologies. We hereby present a case of triple septated concha bullosa that has not been reported so far.